Environmental drivers of the seasonal exposure to airborne Alternaria spores in Spain. - Picornell Rodríguez, Antonio; Rojo, Jesús; Trigo-Pérez, María del Mar; Ruiz-Mata, Rocío; Lara, Beatriz; Romero-Morte, Jorge; Serrano-García, Alicia; Pérez-Badia, Rosa; Gutiérrez-Bustillo, Montserrat; Cervigón-Morales, Patricia; Ferencova, Zuzana; Morales-González, Julia; et al. (Elsevier, 2022)
Alternaria conidia have high allergenic potential and they can trigger important respiratory diseases. Due to that and to their extensive detection period, airborne Alternaria spores are considered as a relevant airborne allergenic particle. Several studies have been developed in order to predict the human exposure to this aeroallergen and to prevent their negative effects on sensitive population. These studies revealed that some sampling locations usually have just one single Alternaria spore season while other locations generally have two seasons within the same year. However, the reasons of these two different seasonal patterns remain unclear. To understand them better, the present study was carried out in order to determine if there are any weather conditions that influence these different behaviours at different sampling locations. With this purpose, the airborne Alternaria spore concentrations of 18 sampling locations in a wide range of latitudinal, altitudinal and climate ranges of Spain were studied. The aerobiological samples were obtained by means of Hirst-Type volumetric pollen traps, and the seasonality of the airborne Alternaria spores were analysed. The optimal weather conditions for spore production were studied, and the main weather factor affecting Alternaria spore seasonality were analysed by means of random forests and regression trees. The results showed that the temperature was the most relevant variable for the Alternaria spore dispersion and it influenced both the spore integrals and their seasonality. The water availability was also a very significant variable. Warmer sampling locations generally have a longer period of Alternaria spore detection. However, the spore production declines during the summer when the temperatures are extremely warm , what splits the favourable period for Alternaria spore production and dispersion into two separate ones, detected as two Alternaria spore seasons within the same year.
Keywords: Hongos - Esporas; Alergia; Ascomicetes - Variaciones estacionales - España; Aerobiology; Fungal spores; Allergy; Seasonality; Weather conditions